Building resilient cities with stringent pollution controls: A case study of robust planning of Shenzhen City's urban agriculture system. (15th August 2021) - Zhou, Yang; Han, Jingcheng; Li, Jie; Zhou, Ya; Wang, Keyi; Huang, Yuefei
Abstract: Building sustainable and resilient cities has become one of the most pressing development challenges facing the world today. Ever-increasing environmental pressures – from emission reduction to pollution prevention – underline the need to balance economic progress with the concern for the environment. Finding new ways of facilitating economic growth within environmental constraints is central to urban sustainable development. In this study, we develop a robust-optimization-based urban agriculture planning (ROB-UAP) model to help decision makers make decisions that are both economically viable and environmentally sustainable. The model enables consideration of more stringent pollution controls in response to the inherent uncertainty in the complex system. Shenzhen City, as the economic engine of the Guangdong-Hong Kong-Macau Greater Bay Area, also faces challenges of urban sustainability transitions. The proposed model is applied to the planning problem of Shenzhen City's urban agriculture system to support environment-oriented agricultural restructuring. We produce six risk-based scenarios to help evaluate the trade-offs between economic returns and environmental impacts. The results show that under expected economic conditions the overall output of the system could be increased by at least 8%, indicating that agricultural restructuring could indeed contribute to the economic growth of the city. In addition, the total amount of the major pollutants could be more or less reduced in the risk-averse and risk-tolerant scenarios; thereby delivering robust decision-making is essential for enabling environmentally low-impact outcomes in planning practices. Graphical abstract: Image 1